VERIFICATION & VALIDATION; AN INCONVENIENT TRUTH. Issue 1 (6th April 2017) - Elich, Erik; Schreinemakers, Paul; Vullings, Maarten
ABSTRACT: This paper addresses several inconveniences regarding the proper use of verification and validation. We address the inconvenient truth by discussing reality in projects and domains, versus the widely accepted definition of verification and validation, versus the way we think both projects and developments should be managed and versus the aim to achieve transparency in the relationship between principals and contractors.